Ecos e silenciamentos na luta do Padre Josimo junto aos movimentos sociais da região do Bico do Papagaio-TO na década de 1980 - Bezerra, Maria do Socorro Soares (2013)
The present dissertation developed in the Graduation Programme in Education at Federal University of Paraíba (PPGE/UFPB), connected to the research line in Popular Education, highlights as a theme Echoes and Silences in the fight of Father Josimo Morais Tavares along with the social movements in the Region of Bico do Papagaio-TO. It points as general objective to analyse the educative dimension of pastoral practice of Father Josimo and his contribution to the process of socio political organization of social rural movements in the region of Bico do Papagaio. Realizing the silence of those who dwelled in the region concerning to the happenings around the fight for agrarian reform and the murders in the countryside, highlighting the case of Father Josimo himself. In this sense I was put up to investigate the contributions made by the church, through the pastoral action of Father Josimo, starting from the assumed that his pastoral work developed by him during 1980 was of relevant meaning. In this work we will discuss about the agrarian issue and the social movement in Brazil and in the state of Tocantins in the decade of 1980. Afterwads we will discuss about the participation of the Catholic Church during 1970 and 1980 decades, the Pastoral Action at Bico do Papagaio and the protagonism of Father Josimo, as well as, we will do a reflexion about the political and pedagogical dimension of the pastoral action. In this study our option was to work with a qualitative approach and, as instruments, we used a semi-structured interview and documental analysis. As a result of Father Josimo pastoral action, we identified that new labour unions were created and those which were already in activity improved a lot in the sense of getting organized and got strengthened in the fight for land, also new comunity associations were created, and, as a consequence of church action, since 1986, the government started to do some land expropriation under the pressure of international organism, in order to settle the families who were displaced by conflicts and have lost their homes at the behest of squatters. Today the region has a significant number of settlements due to the Pastoral action of Father Josimo Morais Tavares.